Management of Ingested Foreign Bodies in Children: A Clinical Report of the NASPGHAN Endoscopy Committee. Issue 4 (April 2015) - Kramer, Robert E.; Lerner, Diana G.; Lin, Tom; Manfredi, Michael; Shah, Manoj; Stephen, Thomas C.; Gibbons, Troy E.; Pall, Harpreet; Sahn, Ben; McOmber, Mark; Zacur, George; Friedlander, Joel; et al.
Abstract : ABSTRACT: Foreign body ingestions in children are some of the most challenging clinical scenarios facing pediatric gastroenterologists. Determining the indications and timing for intervention requires assessment of patient size, type of object ingested, location, clinical symptoms, time since ingestion, and myriad other factors. Often the easiest and least anxiety-producing decision is the one to proceed to endoscopic removal, instead of observation alone. Because of variability in pediatric patient size, there are less firm guidelines available to determine which type of object will safely pass, as opposed to the clearer guidelines in the adult population. In addition, the imprecise nature of the histories often leaves the clinician to question the timing and nature of the ingestion. Furthermore, changes in the types of ingestions encountered, specifically button batteries and high-powered magnet ingestions, create an even greater potential for severe morbidity and mortality among children. As a result, clinical guidelines regarding management of these ingestions in children remain varied and sporadic, with little in the way of prospective data to guide their development. An expert panel of pediatric endoscopists was convened and produced the present article that outlines practical clinical approaches to the pediatric patient with a variety of foreign body ingestions. This guideline is intended as an educational tool that may help inform pediatric endoscopists in managing foreign body ingestions in children. Medical decision making, however, remains a complex process requiring integration of clinical data beyond the scope of these guidelines. These guidelines should therefore not be considered to be a rule or to be establishing a legal standard of care. Caregivers may well choose a course of action outside of those represented in these guidelines because of specific patient circumstances. Furthermore, additional clinical studies may be necessary to clarify aspects based on expert opinion instead of published data. Thus, these guidelines may be revised as needed to account for new data, changes in clinical practice, or availability of new technology. Abstract : Supplemental Digital Content is available in the text